Value of a café‐au‐lait macules screening clinic: Experience from The Hospital for Sick Children in Toronto. Issue 2 (17th February 2022) - Albaghdadi, Mohammed; Berseneva, Maria; Pennal, Alexandra; Wan, Stephanie; Matviychuk, Diana; Shugar, Andrea; Kannu, Peter; Lara‐Corrales, Irene
Abstract: Background/Objectives: Café‐au‐lait macules (CALMs) are a characteristic feature of neurofibromatosis type 1 (NF1), but also occur in other genetic disorders. Differential diagnosis of CALMs remains challenging and can be stressful for families. We sought to examine the role of an established CALMs screening clinic in diagnosing CALMs‐related disorders. Method: We retrospectively reviewed patients seen between July 2012 and January 2019 in a CALMs screening clinic at The Hospital for Sick Children, a tertiary pediatric hospital in Toronto, Canada. Pediatric patients were referred because of multiple CALMs or suspected NF1. Selection was based on a chronological referral sample with no exclusions. A pediatric dermatologist examined all patients for CALMs and NF1 manifestations. Genetic testing was offered to confirm a clinical diagnosis or when clinical findings were inconclusive. Results: Three hundred patients, of which 152 (50.7%) were female and had a mean age of 5.6 ± 4.8 years were seen during the study period. NF1 was diagnosed in 76 (25.3%) patients, mosaic NF1 in 38 (12.7%) patients, and 8 (2.7%) patients received other genetic diagnoses. One hundred and twelve (37.3%) patients were diagnosed with isolated CALMs not associated with an underlying genetic disease. Furthermore, 36 (12%) of our patients did not have CALMs. Conclusions: The CALMs screening clinic aided in the early diagnosis of genetic disorders such as NF1 and distinguished CALMs from other hyperpigmented lesions. We encourage the adoption of this clinic model in referral centers to streamline and optimize care of patients with presumptive diagnosis of CALMs.